Expansive Gender Pedagogy in the Undergraduate Classroom: The Gender and Sexuality Galaxy - Butler, Anne Marie E.; Perry, Margaret (Radical Teacher, 2025)
In a 2023 independent study, students and a professor at a small, predominantly white, undergraduate only, liberal arts college collaborated to design a gender and sexuality worksheet: The Gender and Sexuality Galaxy. The worksheet helps students explore their identities and affinities within attractions, gender expressions, gender identities, sex identities, and sexual identities. The worksheet also allows them to learn how each of these categories is different from the others as well as where these identities and affinities might intersect. Although existing worksheets are well-intentioned, they fall flat on many levels by reinforcing binaries and heteronormativity, and by denying gender expansive, asexual, and trans people a full range of self-expression and identifications. The worksheet uses inclusive self-identification and guided learning approaches to provide space for deep reflection on identities and attractions. Our process in the worksheet research and development and this co-written article follows Diane Fujino et al. (2018) and bell hooks (1994) in conceptualising transformative pedagogy as learning that takes place in a collaborative, socially invested, and socially engaged learning community. This article details the research, development, trial study, and subsequent changes to the worksheet, contextualises it as a pedagogical tool, and discusses how others might use this resource in their classrooms and beyond. We argue that the development of this worksheet, a collaborative, student-centred project, and the resulting article, co-written by professor and student, both enact transformative pedagogy in their processes, and parallel the self-actualisation the worksheet encourages through intersectional learning about expansive ideas of gender, sexuality, and attraction.